2012
DOI: 10.1002/ange.201206055
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Nanocrystals Embedded in a Metal–Organic Framework: Hybrid Hydrogen Storage with Synergistic Effect on Physi‐ and Chemisorption

Abstract: Hydrogen is considered to be a promising energy carrier for the future. In order to use it as a fuel, a compact, safe, and efficient hydrogen storage system should be developed. Porous metal-organic frameworks (MOFs) have attracted great attention as potential hydrogen storage materials, [1] because some MOFs can store large amount of H 2 (> 7 wt %) at 77 K and high pressures. [2] However, at room temperature, the H 2 storage capacities of MOFs drop to less than 1 wt % because interaction energies between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…However, due to their high surface energy and large surface area, the stability of M-NPs is severely decreased, which obstructs the control of size and shape with high uniformity. In particular, the use of M-NPs in porous MOFs with confined void spaces has been proved to be an efficient way of preventing aggregation [1,48,[246][247][248][249][250][251][252]. The nucleation and growth of M-NPs can be averted if the metal or alloy nanoparticles are confined within highly porous scaffold materials, which could be used for the fabrication of metal nanoparticles (NPs) with controlled sizes inside the pores, thereby circumventing a common issue of nanoparticle aggregation [242][243][244][245].…”
Section: Mof-supported Metal Nanoparticle Catalysts For Hydrogen Genementioning
confidence: 99%
“…However, due to their high surface energy and large surface area, the stability of M-NPs is severely decreased, which obstructs the control of size and shape with high uniformity. In particular, the use of M-NPs in porous MOFs with confined void spaces has been proved to be an efficient way of preventing aggregation [1,48,[246][247][248][249][250][251][252]. The nucleation and growth of M-NPs can be averted if the metal or alloy nanoparticles are confined within highly porous scaffold materials, which could be used for the fabrication of metal nanoparticles (NPs) with controlled sizes inside the pores, thereby circumventing a common issue of nanoparticle aggregation [242][243][244][245].…”
Section: Mof-supported Metal Nanoparticle Catalysts For Hydrogen Genementioning
confidence: 99%
“…Guest incorporation can vary greatly and this includes the introduction of nanoparticles, [126][127][128] and organic molecules [129] such as photoswitches, in particular. Such a kind of modulation of adsorption properties of MOFs may be called guest-assisted adsorption.…”
Section: Guest-assisted Adsorptionmentioning
confidence: 99%
“…Such a kind of modulation of adsorption properties of MOFs may be called guest-assisted adsorption. Guest incorporation can vary greatly and this includes the introduction of nanoparticles, [126][127][128] and organic molecules [129] such as photoswitches, in particular. [23]…”
Section: Guest-assisted Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Recently, nanoconfinement has offered new insights and solutions to current hydrogen-storage technology. [9] Theoretical calculations and preliminary experiments have shown that nanoconfined hydrides feature a significantly improved hydrogen-storage performance with respect to their bulk counterparts. [10] Two routes have been widely used to encapsulate hydrogenstorage materials into nanoscaffolds: solution impregnation and melt infiltration.…”
mentioning
confidence: 99%